2020
DOI: 10.3390/ijms21124220
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Annotation of Transposable Elements Revealed a Potential Regulation of Genes Involved in Rubber Biosynthesis by TE-Derived siRNA Interference in Hevea brasiliensis

Abstract: The natural rubber biosynthetic pathway is well described in Hevea, although the final stages of rubber elongation are still poorly understood. Small Rubber Particle Proteins and Rubber Elongation Factors (SRPPs and REFs) are proteins with major function in rubber particle formation and stabilization. Their corresponding genes are clustered on a scaffold1222 of the reference genomic sequence of the Hevea brasiliensis genome. Apart from gene expression by transcriptomic analyses, to date, no deep analyses have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 82 publications
4
9
0
Order By: Relevance
“…It has been well established that TEs are abundant in the rubber tree genome, and the proportion of TE types found in our study was similar to those found by other authors (Liu et al, 2020b; Tang et al, 2016; Wu et al, 2020). Responsible for major changes in the genetic architecture (e.g., rearrangements, duplication, gene breaking, and the origin of new genes) (Bennetzen, 2005; Flagel and Wendel, 2009; Lisch, 2013), TEs are usually neutral.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It has been well established that TEs are abundant in the rubber tree genome, and the proportion of TE types found in our study was similar to those found by other authors (Liu et al, 2020b; Tang et al, 2016; Wu et al, 2020). Responsible for major changes in the genetic architecture (e.g., rearrangements, duplication, gene breaking, and the origin of new genes) (Bennetzen, 2005; Flagel and Wendel, 2009; Lisch, 2013), TEs are usually neutral.…”
Section: Discussionsupporting
confidence: 92%
“…Responsible for major changes in the genetic architecture (e.g., rearrangements, duplication, gene breaking, and the origin of new genes) (Bennetzen, 2005; Flagel and Wendel, 2009; Lisch, 2013), TEs are usually neutral. However, such elements possess mutagenic potential due to epigenetic mechanisms and are able to alter regulatory networks and confer genetic adaptations, leading to important phenotypic variations (Lisch, 2013; Wei and Cao, 2016; Wu et al, 2020); this has currently received great attention in genetic improvement programs for several species (Domínguez et al, 2020; Lee et al, 2006; Wang et al, 2020). In Hbr, Wu et al (2020) showed that TEs located in gene regulatory regions in Hbr were involved in latex production through cis regulation, which would explain the differential gene expression among contrasting genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These TEs have already been described as being involved in gene expression, responses to external stimuli and plant development (Kashkush et al, 2003;Matsunaga et al, 2015;Traylor-Knowles et al, 2017;Tran and Choi, 2020). In rubber trees, TEs may be related to the differential expression observed in some commercial clones, affecting important processes such as rubber production (Wu et al, 2020a). As pointed out by Wang et al (2020), the identification of TEs associated with functional genes related to important characteristics suggest that they can be used as molecular markers in MAS, contributing significantly to the genetic improvement of woody trees.…”
Section: Multiomicsmentioning
confidence: 96%
“…This approach has become increasingly common in humans (Wu et al, 2018), animals (Fonseca et al, 2018), microorganisms (Wang et al, 2019), and combinations of species (Pinu et al, 2019). However, for plants, such integrated methodologies are still a great challenge, especially for nonmodel species with elevated genetic diversity and complex genomes (Jamil et al, 2020), which is the case for H. brasiliensis (Tang et al, 2016;Liu et al, 2020c, Wu et al, 2020a. Despite its economic importance, no study incorporating multiomics has been carried out on H. brasiliensis.…”
Section: Introductionmentioning
confidence: 99%